What Is the Influence of Morphological Knowledge in the Early Stages of Reading Acquisition Among Low SES Children? A Graphical Modeling Approach - Colé, Pascale; Cavalli, Eddy; Duncan, Lynne G.; Theurel, Anne; Gentaz, Edouard; Sprenger-Charolles, Liliane; El-Ahmadi, Abdessadek (Frontiers in Psychology, 2018)
Children from low-SES families are known to show delays in aspects of language development which underpin reading acquisition such as vocabulary and listening comprehension. Few studies have focused on the development of morphological skills in this group, and none in French. The present study investigated the involvement of morphological knowledge in the very early stages of reading acquisition (decoding), before reading comprehension can be reliably assessed. We assessed listening comprehension, receptive vocabulary, phoneme awareness, morphological awareness as well as decoding, word reading and non-verbal IQ in 703 French first-graders from low-SES families after 3 months of formal schooling (November). Awareness of derivational morphology was assessed using three oral tasks: Relationship Judgment (e.g. do these words belong to the same family or not? heat-heater ….ham-hammer); Lexical Sentence Completion (e.g. Someone who runs is a …? (runner)); and Non-lexical Sentence Completion (e.g. Someone who lums is a…? (lummer)). The tasks differ on implicit/explicit demands and also tap different kinds of morphological knowledge. The Judgement task measures the phonological and semantic properties of the morphological relationship and the Sentence Completion tasks measure knowledge of morphological production rules. Data were processed using a graphical modelling approach which offers key information about how skills known to be involved in learning to read are organized in memory. This modelling approach was therefore useful in revealing a potential network which expresses the conditional dependence structure between skills, after which recursive structural equation modelling was applied to test specific hypotheses. Six main conclusions can be drawn from these analyses about low SES reading acquisition: 1) listening comprehension is at the heart of the reading acquisition process; 2) word reading depends directly on phonemic awareness and indirectly on listening comprehension; 3) decoding depends on word reading; 4) Morphological awareness and vocabulary have an indirect influence on word reading via both listening comprehension and phoneme awareness; 5) the components of morphological awareness assessed by our tasks have independent relationships with listening comprehension; and 6) neither phonemic nor morphological awareness has a direct influence on vocabulary. The implications of these results with regard to early reading acquisition among low SES groups